2020
DOI: 10.1088/1361-6560/aba7d0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of a coincidence time resolution metric including depth-of-interaction bias for TOF-PET

Abstract: Depth-of-interaction (DOI) variability of annihilation photons is known to be a source of coincidence time resolution (CTR) degradation for fast time-of-flight–positron emission tomography detectors. An analytical model was recently proposed to explicitly include the DOI time bias separately from variance-related statistical factors, such as scintillation photon emission and photosensor jitter, in the CTR evaluation. In the present work, an experimental validation of this new model is provided. An unconvention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Indeed, even with instantaneous emission and zero-jitter timing photodetection, reaching 10 ps CTR remains inaccessible because of the DOI variability between coincidence events. A DOI difference between two coincident detectors was shown to induce a bias that degrades the timing accuracy, hence the overall CTR for all DOI combinations (Toussaint et al 2019, Loignon-Houle et al 2020. Also, a well-known problematic effect of DOI variability is the parallax effect which degrades the radial spatial resolution uniformity (MacDonald and Dahlbom 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, even with instantaneous emission and zero-jitter timing photodetection, reaching 10 ps CTR remains inaccessible because of the DOI variability between coincidence events. A DOI difference between two coincident detectors was shown to induce a bias that degrades the timing accuracy, hence the overall CTR for all DOI combinations (Toussaint et al 2019, Loignon-Houle et al 2020. Also, a well-known problematic effect of DOI variability is the parallax effect which degrades the radial spatial resolution uniformity (MacDonald and Dahlbom 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In realistic TOF-PET detectors, the variation of and the optical transfer can give rise to three causes of time resolution loss: 1) the dependence of the average optical transfer time (from to the photosensor) on ; 2) the OTTS for a given , as determined by the detector geometry and the properties of the optical interfaces; and 3) the variation of the OTTS with . Toussaint et al [ 36 ], Loignon-Houle et al [ 37 ] showed that the incorporation of these effects in the CRLB is nontrivial, but still arrived at a useful expression for the time resolution achievable with high-aspect-ratio crystals. It is possible to generalize Toussaint’s equation such that it also applies to other types of crystal, for example monolithic scintillator detectors [ 28 ].…”
Section: Time Resolutionmentioning
confidence: 99%
“…21,32 Multiple approaches have been explored over the years to incorporate the DOI-induced error into the analytical modeling of timing resolution in PET detectors. 21,33,34 Our contribution to mitigate this degrading effect is integrating the DOI-dependent timestamps correction into the calculation of timing resolution which resulted in an enhanced timing resolution for our Prism-PET prototype scanner. 28 When scintillation photons are generated within a crystal column in a Prism-PET detector module, some photons travel downward to trigger the primary SiPM (i.e., primary pixel) and some travel upward to the light guide which are then steered to the nearestneighboring crystals and travel downward to trigger the nearest-neighboring SiPMs (i.e., secondary pixels, see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Reaching a high TOF gain requires mitigating the DOI‐induced bias on timing resolution (in the order of 150–200 ps) since coincidence events at different DOIs can lead to biased estimation of photon arrival times, especially for long crystals (15–25 mm) 21,32 . Multiple approaches have been explored over the years to incorporate the DOI‐induced error into the analytical modeling of timing resolution in PET detectors 21,33,34 . Our contribution to mitigate this degrading effect is integrating the DOI‐dependent timestamps correction into the calculation of timing resolution which resulted in an enhanced timing resolution for our Prism‐PET prototype scanner 28 …”
Section: Introductionmentioning
confidence: 99%